Rapid human subjects research in times of disruption - LeNoble, Chelsea A.; Horan, Kristin A.; Steigerwald, Nina (Frontiers in Sociology, 2022)
One significant challenge facing the implementation of rapid research studies, or research that responds quickly to societal needs, involves the recruitment and retention of human subjects research participants. The purpose of this paper is to offer insights into the nuances of conducting rapid research during times of disruption. The first-hand accounts of participants experiencing disruption are critical and perishable. Although it may be difficult to recruit and retain participants, their data are needed to best understand and learn from novel, unprecedented situations. To this end, the authors draw from and analyze their experience conducting rapid research funded by the National Science Foundation to examine the effects of the COVID-19 pandemic on undergraduate education. The paper begins with a summary of the rapid project aims and research questions. Then, participant recruitment and retention challenges are briefly introduced as an advanced organizer of the paper. From there, the paper is structured in three sections that represent the human subjects research challenges faced during rapid study implementation. In the discussion, the authors summarize the above challenges and lessons learned in the larger context of rapid research. They reflect on a sometimes-forgotten issue: the wellbeing of research team members who face these and other salient challenges reflective of navigating life during a worldwide pandemic. By describing human subjects research challenges experienced in the implementation of a rapid study and lessons learned from experiencing and adapting to these challenges, this paper contributes meaningful insights into the daily challenges of carrying out rapid research.